Evolution of health system resources and factors associated with the quality of care for epidemic-prone diseases in Guinea: a national cross-sectional study - Dimaï Ouo Kpamy; Fatoumata Cherif; Sory Conde; Fodé Amara Traore; Sidikiba Sidibe; Bassirou Diarra; Peter John Winch; Abdoulaye Toure; Sakoba Keita; Seydou Doumbia; Alexandre Delamou (Frontiers in Epidemiology, 2026)
Objective This study aimed to describe the evolution of resources for the management of epidemic-prone diseases and to identify the factors associated with the quality of care for epidemic-prone diseases in Guinea. Methods A descriptive and analytical cross-sectional study was conducted to assess the management system for epidemic-prone diseases in Guinea. Data were collected using structured questionnaires and supplemented by a review of official documents to assess the evolution of resources before, during, and after the 2014–2016 Ebola virus disease outbreak. Factors associated with the quality of care were identified using multivariable logistic regression analysis. Results The evolution of resources varied across the different health regions. At the national level, the overall resource score increased from 12% before the Ebola outbreak to 73% during the outbreak and reached 77% in the post-Ebola period. Overall, the quality of care was rated as good in 60.5% of health facilities. Five factors were independently associated with good-quality care: the presence of a patient diagnostic mechanism (aOR = 3.17; 95% CI: 1.74–5.57; p < 0.001), the availability of treatment protocols (aOR = 2.42; 95% CI: 1.27–4.61; p = 0.007), the existence of patient isolation facilities (aOR = 4.76; 95% CI: 1.72–13.17; p = 0.003), effective coordination of case management (aOR = 3.04; 95% CI: 1.10–8.39; p = 0.031), and the availability of dedicated case management teams (aOR = 8.51; 95% CI: 4.07–17.76; p < 0.001). Conclusion This study highlights a substantial improvement in the resources allocated to the management of epidemic-prone diseases in Guinea following the Ebola virus disease outbreak, reflecting strengthened health system capacity for epidemic preparedness and response. However, sustaining these gains will require continued investment, particularly in health system financing. Strengthening diagnostic capacity, ensuring the availability of standardized treatment protocols, expanding patient isolation facilities, improving coordination mechanisms, and maintaining specialized case management teams should remain strategic priorities to enhance the quality of care and strengthen the resilience of the health system against future epidemics.